Epigenetic IVD Tests for Personalized Precision Medicine in Cancer - Beltrán-García, Jesús; Osca-Verdegal, Rebeca; Mena-Mollá, Salvador; García-Giménez, José Luis (Frontiers in Genetics, 2019)
Epigenetic alterations play a key role in the initiation and progression of cancer. Therefore, it is possible to use epigenetic marks as biomarkers for predictive and precision medicine in cancer. Precision medicine is poised to impact clinical practice, patients and healthcare systems. The objective of this review is to provide an overview of the epigenetic testing landscape in cancer by examining commercially available epigenetic-based in vitro diagnostic tests for colon, breast, cervical, glioblastoma, lung cancers, and for cancers of unknown origin. We compile current commercial epigenetic tests based on epigenetic biomarkers (i.e. DNA methylation, miRNAs, and histones) that can actually be implemented into clinical practice.